Design and fabrication of a haptic touch sensor for soft robotic applications - Tay, Sean Wei Sheng (Nanyang Technological University, 2024)
Flexible pressure sensors have emerged as a promising field with diverse applications ranging from healthcare to industrial automation. The integration of these sensors capable of detecting touch and pressure plays a crucial role in enhancing the effectiveness of various systems. Different levels of pressure applied can be used to identify an object and discern certain qualities it has, such as its shape, texture, and hardness. This capability enables tasks such as object recognition, manipulation, and grasping to be performed. The focus of this project is to design and fabricate haptic touch sensors for flexible pressure sensor applications. Different materials will be taken into consideration for the sensor, and experiments will be conducted to create the most optimal sensor with a broad sensing range, high sensitivity, and durability for its practical applications.